Christianization and Colonialism in Africa Between the 19th and 20th Centuries - benbouzid, lakhdar (Journal of Social Sciences and Humanities, 2016)
The conflict between Islam and Christianity began with the rise of Islam, as Muslims fought their first wars against the Byzantines in the Battle of Mu'tah. This was followed by the Islamic conquests, where Islam spread into the Christian world in North Africa and Syria, including Palestine and Asia Minor. From Morocco, Muslims crossed into Spain and then into France, where they were halted by the Franks at the Battle of Tours (Poitiers). Approximately four centuries later, Europe launched campaigns against the Islamic world known as the "Crusades," though the Europeans achieved little in those wars, which lasted for two centuries. Later, the conflict took a different form; this time, Europe sent missionaries instead of soldiers. Initially, the process of Christianization was unorganized, but it became more systematic over time, coinciding with the emergence of Orientalism and Colonialism. Both played a significant role in the development of missionary work; Colonialism supported Christianization to serve its interests in the Islamic world, while Orientalism—which posed a major threat to Islam—also served missionary efforts by paving the way for proselytizers. Despite extensive efforts, missionaries did not achieve their goals in the Islamic world; however, they succeeded in vast regions of Sub-Saharan Africa, as well as East and South Asia.